2006
DOI: 10.1111/j.1600-0765.2006.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes related to mechanical stress in human periodontal ligament cells using microarray analysis

Abstract: Our microarray is the first to show the gene profile in PDL cells caused by mechanical stress; however, further studies to clarify the physiological function of these molecules in PDL cells are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 56 publications
3
39
0
1
Order By: Relevance
“…IL-6 is a strong osteoclast activator (22) that increase in PDL http://bmbreports.org cells in response to static compressive force (5,6). IL-6 decreased in expression after 12 hours of static tensional force ( Table 2).…”
Section: Genes Related To New Bone Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-6 is a strong osteoclast activator (22) that increase in PDL http://bmbreports.org cells in response to static compressive force (5,6). IL-6 decreased in expression after 12 hours of static tensional force ( Table 2).…”
Section: Genes Related To New Bone Formationmentioning
confidence: 99%
“…Recently, the molecular mechanism of bony resorption in the compressive side was investigated by DNA microarray technology and a threedimensional cell culture system (5,6). There it was shown the expression of interleukin-6 (IL-6), a strong osteoclastogenesisactivating cytokine, increased in response to a static compressive force in PDL cells (5,6). Moreover, the activity of alkaline phosphatase (ALP) in PDL cells decreased by the same static compressive force (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, this distinction extends to inflammatory mediators as well. Static compression can upregulate IL-6 (40), PGE2, and COX2 (14), supporting the catabolic side of remodeling, whereas tension can suppress IL-1b-induced upregulation of PGE2, COX2, and MMP-1 and -3 (43).…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, de Araujo et al (33) reported a microarray analysis of human PDL cells under compressive forces using an in vitro three-dimensional culture system. They identified several up-regulated genes, including inflammation-related molecules, such as COX-2 (cyclooxygenase-2), PGE 2 (prostaglandin E 2 ), IL-6 (interleukin-6), and IL-1␤ (interleukin-1␤), which were not listed in our present study.…”
Section: Discussionmentioning
confidence: 99%